THE EFFECT OF ENTREPRENEURIAL ORIENTATION, PARTNERSHIP, AND BRAND EQUITY ON BUSINESS PERFORMANCE IN MSMES IN SEMARANG CITY - Pudjonarko, Cahyamas Arif Satria; Perdana, Mirwan Surya (Jurnal Sains Pemasaran Indonesia (Indonesian Journal of Marketing Science), 2025)
This study aims to analyze the influence of Entrepreneurial Orientation (EO), Partnership, and Brand Equity on Business Performance in MSMEs in Semarang City. The method used is quantitative with a SmartPLS approach. The results show that EO has a significant effect on Partnership, Partnership has a significant effect on Brand Equity and Business Performance, and Brand Equity also has a significant effect on Business Performance. This study emphasizes the importance of synergy among variables in improving the business performance of SMEs.